malondialdehyde (MDA) and reduces glutathione (GSH) levels in maternal and umbilical serum in women with mild and moderate pre-Eclampsia - Al-shawi, nada. Naji (Journal of the Faculty of Medicine Baghdad, 2006)
Background: